Calgary's Pedestrian Strategy: Inception to Implementation (breakout presentation). (December 2017) - Chapman, Jonathan; Olson, Joe
Abstract : Background: At the direction of the GM of Transportation, City staff were tasked in late 2014 with the development of a comprehensive strategy to improve safety and encourage more Calgarians to walk. The strategy was to include a vision, principles, actions, and staffing and funding requirements. The challenges were many: How do we effectively collaborate across so many internal service providers?; How do we engage the public and effectively use their input?; How do we identify the real vs perceived barriers to walking?; What are effective actions to lower pedestrian injury rates or incite more walking?; How do we set aggressive, but attainable targets?; How do we demonstrate good return on investment?; How do we make the case for dedicated staffing? Description of Program: The project team took a multi-faceted approach to developing a strategy, tying together broad internal consultation (to understand existing services and identify gaps), key themes and concerns arising from public engagement, best practices from other cities, opportunities for partnerships, and a careful assessment of the objectives and how to measure results over time. A prioritization matrix was developed to identify the most feasible and impactful actions. The final strategy was approved (with one significant amendment) in May of 2016. Outcomes: As a result of the strategy, the City has been able to achieve better alignment and project collaboration. Permission space allowed us to instigate a new tactical urbanism effort, experiment with new treatments and controls, and develop a research agenda to explore outstanding questions. At the same time, economic tides have limited our ability to develop a core team, and some efforts are still challenged by autocentric structures and systems of reward within the corporation. Implications: There are many North American jurisdictions with similar challenges - auto-oriented urban form, complex bureaucracies, constrained budgets, and a desire to change course. Conducted well, the process of developing a strategy can itself spark institutional change, raise public consciousness, create momentum, build partnerships, and establish a foundation for nimble and effective change over time.